Knowledge, attitude and practices studies conducted amongst medical students of India - Sachdeva, Sandeep; Taneja, Neha; Dwivedi, Nidhi (International Journal Of Community Medicine And Public Health, 2018)
Background: Assessment of published original “KAP” based research studies conducted amongst Indian medical undergraduate students. Methods: A systematic evaluation was undertaken using keywords “KAP” or “knowledge” or “awareness” or “attitude” or “practices” and “MBBS students” or “medical students” or “health students” or “undergraduate student” or “university students” and “India” through search engines, PUBMED and Google scholar under certain criteria. Results: Highest, “KAP” based articles amongst MBBS students published during one-year period were related to Pharmacovigilance (15.6%) followed by organ/blood donation (11.7%) and self-medication (9.8%), tobacco (5.8%), and basic life support (5.8%) etc; 48 (94.1%) article was one-time cross-sectional descriptive studies while 03 (5.8%) had intervention based research design. Average no. of authors per article was 3.5 (±1.3); Medical student was co-author in 04 (7.8%) research papers. Corresponding author was largely dominated by faculties from pre and para-clinical departments with highest from pharmacology (29.4%) and community medicine (27.4%). The studies covered an average sample size of 225.8 MBBS students (45-648, range) per research article. Avg. no. of references used/article was 18.6 (±7.4); Out of all the references used in research articles, only 60.2% were of recent-10 year time frame (2007-2016) origin while the rest were from older time-frame and only 36.1% of all the references were of Indian origin. Conclusions: Probably, first of its kind systemic synthesis undertaken in the country concludes that diverse topics of “KAP” research have been conducted by the teaching faculties on MBBS students in India and this study provides the over-view of the same.